Вплив виробничо-економічних факторів на якість життя населення адміністративних районів Волинської області - Краснопольська, Надія Володимирівна; Швець, Тетяна Юріївна; Krasnopolska, Nadiia V.; Shvets, Tetiana Yu. (Сумський державний педагогічний університет імені І. С. Макакренка, 2015)
Розглянуто особливості впливу зовнішніх факторів на формування показників рівня і якості життя населення адміністративних районів Волинської області. Проаналізовано овновні показники виробничо-економічних факторів, а саме, структуру та рівень зайнятості населення, структуру та спеціалізацію господарства, фінансове забезпечення та рівень соціально-економічного розвитку регіону.

The peculiarities of the influence of external factors on the formation of indicators of the level and quality of life of the population of the administrative districts of Volyn region. Analyzed the main indicators of production and economic factors, namely the structure and level of employment, the structure and specialization of the economy, financial support (investment) and the level of socio-economic development of the region. A comparative analysis of some indicators of production and economic factors affecting the standard of living of the population. On the basis of statistical indicators method of ranking conducted by grouping the administrative districts of Volyn region on production and economic indicators. Identify leading administrative areas are relatively better development of living standards. Identified priority areas for regional policy aimed at improving the performance of the economic complex of the region with the aim of raising the level and quality of life of the population.
The Impact оf Production-Economic Factors оn the Quality of Life of the Population of the Administrative Districts of Volyn Region
Keywords: фактори; якість життя; населення; адміністративні райони